Determinants of Firm Value Based on Macro and Micro Dynamics: Inflation and Financial Performance as Moderating Variables - Siti Aisyah; Johny Aninam; Mekar Meilisa Amalia; Neti Erlina; Novitasari (LP2M IAIN Palopo, 2026)
This study aims to analyze the influence of macroeconomic and microeconomic dynamics on firm value through a dual moderation model. Specifically, this study examines how macroeconomic variables (such as exchange rates and interest rates) affect firm value, with inflation as a moderating variable, and how microeconomic fundamental factors affect firm value, with financial performance as a moderating variable. Using a quantitative approach with the Structural Equation Modeling (SEM) method, this study integrates Signaling Theory and Arbitrage Pricing Theory to explain the phenomenon of capital market volatility. The analysis results indicate that inflation plays a crucial role in weakening the transmission of monetary stability to firm value, while solid financial performance has been shown to strengthen market appreciation of the issuer's intrinsic value. This study provides a theoretical contribution to the financial management literature regarding the interaction between systematic risk and firm-specific risk in determining shareholder value in emerging markets.